Nucleation and development of Goss texture and magnetic induction in thin-gauged 3% Si-Fe alloy - Heo, NH; Chai, KH; Na, JG; Kim, J; Woo, JS (AMER INST PHYSICS, 1999)
Nucleation and development of Goss texture have been investigated in high-purity 3% silicon-iron alloy strips. During final annealing, under a high vacuum, Goss texture can form independently from cold-rolled matrix at the early stage of primary recrystallization, regardless of any pre-existing Goss texture near the strip surface. The formation mechanism of the new Goss texture probably follows the oriented nucleation theory, which is due to segregated sulfur present on the strips in a final annealing time. Goss texture in the primary recrystallization develops into the final Goss texture or not, depending on cold rolling conditions. (C) 1999 American Institute of Physics. [S0021-8979(99)18408-1].